2003
DOI: 10.1021/ja0268635
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptide-Membrane Interactions:  Glycosyl Enkephalin Analogues Adopt Turn Conformations by NMR and CD in Amphipathic Media

Abstract: Four enkephalin analogues (Tyr-D-Thr-Gly-Phe-Leu-Ser-CONH(2), 1, and the related O-linked glycopeptides bearing the monosaccharide beta-glucose, 2, the disaccharide beta-maltose, 3, and the trisaccharide beta-maltotriose, 4) were synthesized, purified by HPLC, and biophysical studies were conducted to examine their interactions with membrane model systems. Glycopeptide 2 has been previously reported to penetrate the blood-brain barrier (BBB), and produce potent analgesia superior to morphine in mice (J. Med. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 83 publications
0
62
0
Order By: Relevance
“…BBB penetration studies of glycopeptides have indicated up to a 3-fold increase in the rate of brain delivery of these compounds compared with the unglycosylated parent peptides (Bilsky et al, 2000;Egleton et al, 2000Egleton et al, , 2001. Recent studies with glycopeptides in artificial membrane systems indicate that the amphipathicity of the glycopeptides may be an important factor in BBB penetration (Palian et al, 2003). In addition, there is evidence that suggests that the type of glycosylation can alter tissue distribution patterns (Susaki et al, 1999;Suzuki et al, 1999a,b), BBB penetration unpublished results), and peptide/receptor interactions (Gysin and Schwyzer, 1983;Sargent et al, 1988;Palian and Polt, 2001).…”
mentioning
confidence: 99%
“…BBB penetration studies of glycopeptides have indicated up to a 3-fold increase in the rate of brain delivery of these compounds compared with the unglycosylated parent peptides (Bilsky et al, 2000;Egleton et al, 2000Egleton et al, , 2001. Recent studies with glycopeptides in artificial membrane systems indicate that the amphipathicity of the glycopeptides may be an important factor in BBB penetration (Palian et al, 2003). In addition, there is evidence that suggests that the type of glycosylation can alter tissue distribution patterns (Susaki et al, 1999;Suzuki et al, 1999a,b), BBB penetration unpublished results), and peptide/receptor interactions (Gysin and Schwyzer, 1983;Sargent et al, 1988;Palian and Polt, 2001).…”
mentioning
confidence: 99%
“…143 Perhaps, we can explain this by Schwyzer's membrane compartment theory, which suggests that the MOR binding site resides in a more hydrophilic environment than the binding site for the DOR. 13 Nevertheless, another point should be highlighted here is that the position of the carbohydrate moiety, type of linkage used, and the kind of sugar moiety introduced are of major consequence to bioactivities of these compounds.…”
Section: B Glycosylationmentioning
confidence: 99%
“…126 That is, the amphipathic glycopeptides possess 2 confl icting solubility states: one state that is completely water soluble, and another at water-membrane phase boundaries. However, simply producing highly amphipathic sequences is not enough to promote systemic delivery and penetration of the BBB.…”
Section: E81mentioning
confidence: 99%